Relationships between anaemia and parasitic infections in Kenyan schoolchildren: A Bayesian hierarchical modelling approach - Koukounari, Artemis; Estambale, Benson B.; Njagi, J.Kiambo; Cundill, Bonnie; Ajanga, Anthony; Crudder, Christopher; Otido, Julius; Jukes, Matthew C.H.; Clarke, Siân E.; Brooker, Simon (Elsevier, 2008)
Anaemia is multi-factorial in origin and disentangling its aetiology remains problematic, with surprisingly few studies investigating the relative contribution of different parasitic infections to anaemia amongst schoolchildren. We report cross-sectional data on haemoglobin, malaria parasitaemia, helminth infection and undernutrition among 1523 schoolchildren enrolled in classes 5 and 6 (aged 10–21 years) in 30 primary schools in western Kenya. Bayesian hierarchical modelling was used to investigate putative relationships. Children infected with Plasmodium falciparum or with a heavy Schistosoma mansoni infection, stunted children and girls were found to have lower haemoglobin concentrations. Children heavily infected with S. mansoni were also more likely to be anaemic compared with uninfected children. This study further highlights the importance of malaria and intestinal schistosomiasis as contributors to reduced haemoglobin levels among schoolchildren and helps guide the implementation of integrated school health programmes in areas of differing parasite transmission.
https://doi.org/10.1016/j.ijpara.2008.05.013
Keywords: Anaemia; Haemoglobin concentration; Malaria; Helminth infections; Bayesian hierarchical models; School children; Kenya